1992
DOI: 10.1172/jci115889
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine profiles in experimental human malaria. Relationship to protection and disease course after challenge.

Abstract: Serum cytokine profiles were evaluated in immunized and nonimmunized human volunteers after challenge with infectious Plasmodium falciparum sporozoites. Three volunteers had been immunized with x-irradiated sporozoites and were fully protected from infection. Four nonimmune volunteers all developed symptomatic infection at which time they were treated.Sera from all volunteers were collected at 20 time points during the 28-d challenge period; levels of IL-la, IL-1,#, IL-2, IFN-'y, tumor necrosis factor-a, IL-4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 65 publications
1
44
1
2
Order By: Relevance
“…7 These observations agree with previous conclusions based on pathologic studies of humans and murine models that implicate an overproduction of proinflammatory and TH-1 cytokines as an important factor in the immunopathogenesis of cerebral malaria. 7,[13][14][15][16][17][18]22 Results of this study indicate differences in local cytokine response in various regions of the brain after plasmodial infection. The proinflammatory cytokines (IL-1␤ and TNF-␣) and TH-1 cytokine (IFN-␥) had the highest levels of mRNA expression in the cerebellum during late P. coatneyi infection in rhesus monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…7 These observations agree with previous conclusions based on pathologic studies of humans and murine models that implicate an overproduction of proinflammatory and TH-1 cytokines as an important factor in the immunopathogenesis of cerebral malaria. 7,[13][14][15][16][17][18]22 Results of this study indicate differences in local cytokine response in various regions of the brain after plasmodial infection. The proinflammatory cytokines (IL-1␤ and TNF-␣) and TH-1 cytokine (IFN-␥) had the highest levels of mRNA expression in the cerebellum during late P. coatneyi infection in rhesus monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have also reported a putatively protective role of IL-6 during malarial infection. For example, an early increase in IL-6 was recorded in volunteers vaccinated with irradiated sporozoites and later challenged with Plasmodium falciparum (52). These volunteers were fully protected from malarial infection.…”
Section: Figmentioning
confidence: 99%
“…Furthermore, it is becoming clear that innate responses can differ between individuals (25,36) with potential clinical implications. To date, only two-rather small-studies have exploited the unique opportunity offered by experimental infection of malaria-naive volunteers (during the evaluation of antimalarial vaccines) to study the very early stages of the immune response to malaria (37,38), and it has been difficult to draw any generalizable conclusions from them. Here, we present a detailed longitudinal analysis of 11 different cytokine responses in 18 experimentally infected individuals, using a highly sensitive, bead-based multiplex assay, and we compare these responses with peripheral parasite densities, as measured by quantitative real-time PCR (39).…”
Section: R Esearch On the Immunology Of Malaria Infection Has Beenmentioning
confidence: 99%